Constituição identitária docente e o trabalho formativo do coordenador pedagógico: relações que transformam - Marella, Tainá Gonçalves (2025)
The experiences lived within the school context deeply mark the trajectory of teachers, especially when crossed by hierarchical relationships, traditional management models, and conceptions that impact the appreciation of teaching work. In this context, the pedagogical coordinator plays a significant role, which may either promote environments of listening and professional growth or reinforce structures of silencing and insecurity. Considering that the process of teacher identity constitution is relational, this research seeks to understand how the actions and the relationship with the pedagogical coordinator influence professional development and the way teachers perceive themselves as subjects of educational practice. The general objective of this study is to identify and analyze the influence of the pedagogical coordinator's actions and relationship on the development of teaching practices and on how teachers perceive or see themselves as professionals. The specific objectives include: understanding how teachers perceive the role of the pedagogical coordinator throughout their trajectory; analyzing how they describe and assign meaning to this role in the school context; identifying practical actions of the coordinator that influence professional development and impact teacher identity; and investigating the characteristics of the teacher–coordinator relationship that positively or negatively affect their practice and identity. The research adopts a qualitative approach, through reflective interviews with five teachers working in a private school in the city of São Paulo, Brazil. The narratives were analyzed using prosaic analysis, aiming to interpret the meanings produced by the participants about their professional trajectory, the impacts of the pedagogical coordinator's actions, and the marks left by the relationships established in daily school life. The theoretical framework draws on authors such as Claude Dubar, who understands identity as a social construction mediated by interactions; Paulo Freire, who emphasizes the centrality of dialogue and the appreciation of the subject in educational practice; and Vera Placco, Vera Trevisan de Souza, and Laurinda Almeida, who discuss the multiple dimensions of the pedagogical coordinator’s formative and articulating role in the school. The research shows that the relationship with the pedagogical coordinator can function either as a mirror or a rupture, promoting both recognition and professional strengthening, or experiences of devaluation and insecurity, especially in contexts marked by institutional authoritarianism